Perioperative emergency laparotomy pathway for patients undergoing emergency laparotomy: A propensity score matched study - Joel Wen Liang Lau; Janardhan Baliga; Faheem Khan; Ying Xin Teo; Jonathan Ming Jie Yeo; Vincent Zhiwei Yeow; Christine Xia Wu; Stephanie Teo; Tracy Jia Hui Goh; Philip Iau; Emergency Laparotomy Group (Annals, Academy of Medicine, Singapore)
Introduction: Emergency laparotomy (EL) is associated with high morbidity and mortality, often exceeding 10%. This study evaluated the impact of the EMergency Laparotomy Audit (EMLA) interdisciplinary perioperative pathway on patient outcomes, hospital costs and length of stay (LOS) within a single centre. Method: A prospective cohort study was conducted from August 2020 to July 2023. The intervention team included specialist clinicians, hospital administrators and an in-hospital quality improvement team. Patients who underwent EL were divided into a pre-intervention control group (n=136) and a post-intervention group (n=293), and an 8-item bundle was implemented. Propensity scoring with a 1:1 matching method was utilised to reduce confounding and selection bias. The primary outcomes examined were LOS, hospitalisation costs and surgical morbidity, while secondary outcomes included 30-day mortality and adherence to the intervention protocol. Results: The utilisation of the EMLA perioperative care bundle led to a significant reduction in surgical complications (34.8% to 20.6%, <P=0.01), a decrease in LOS by 3.3 days (15.4 to 12.1 days, P=0.03) and lower hospitalisation costs (SGD 40,160 to 30,948, P=0.04). Compliance with key interventions also showed improvement. However, there was no difference in 30-day mortality. Conclusion: This study offers insights on how surgical units can implement systemic perioperative changes to improve outcomes for patients undergoing emergency laparotomy.